Conceptual problems surrounding intangible cultural heritage in international law (Journal of Human Sciences, 2022)
This The protection of the intangible cultural heritage represents one of the most important challenges that members of the international community have had to raise in recent years, due to the difficulty that accompanied the international efforts that were made to preserve the various components of the intangible cultural heritage, which became more complex after the effects of globalization spread through the society of some countries. Which failed to address the demise of the most important features of its intangible cultural heritage of customs, traditions, and knowledge passed down generation after generation since ancient times. The de facto situation has led to a redoubling of efforts exerted at the legal level, especially within the framework of international law, to put an end to this negative phenomenon, and to surround this basic aspect of cultural heritage with adequate protection from threats to it.